Respuesta :

Answer:   1. 29/8

                2. 37.72

                3. 24

Step-by-step explanation:

1. x + 1 3/8 = 2 1/4

              x = 21/4 - 13/8

              x = 42/8 - 13/8           [set the denominator equal]

              x = 29/8

2. 13.27 = t - 24.45

Rewrite the function as t - 24.45 = 13.27

                                                   t  = 13.27 + 24.45

                                                   t  = 37.72              

3.  9 = 3/8 × y

Rewrite as 3/8 x y = 9

                            y = 9/ (3/8)

                            y = 9 x (8/3)

                            y = 24